If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 9z + -3z + 2 + -6z + 4 + z Reorder the terms: 2 = 2 + 4 + 9z + -3z + -6z + z Combine like terms: 2 + 4 = 6 2 = 6 + 9z + -3z + -6z + z Combine like terms: 9z + -3z = 6z 2 = 6 + 6z + -6z + z Combine like terms: 6z + -6z = 0 2 = 6 + 0 + z 2 = 6 + z Solving 2 = 6 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. 2 + -1z = 6 + z + -1z Combine like terms: z + -1z = 0 2 + -1z = 6 + 0 2 + -1z = 6 Add '-2' to each side of the equation. 2 + -2 + -1z = 6 + -2 Combine like terms: 2 + -2 = 0 0 + -1z = 6 + -2 -1z = 6 + -2 Combine like terms: 6 + -2 = 4 -1z = 4 Divide each side by '-1'. z = -4 Simplifying z = -4
| 3m+6m-10m=3+7-4+m | | .4(7-3x)=9+(4x-1) | | 5x+8x+11x= | | -40x+36x=30x-45 | | 2b^2+36-9=0 | | 4x-3=9x+9 | | 5x^3-3x^2-5x+3=5x^2-4x-1 | | y=[100+.75(y-150)]+100+100 | | 2v^2-3v+1=0 | | (x^2)+(11x)=0 | | y=-16+4x | | y=4x+-16 | | 2x+20=60+x | | 4(3x+7)=16 | | x^2-4x^2+3=0 | | (x^2)-(6x)=0 | | (4x^2+2x)(5x-4)= | | -1.5x+y=5 | | (x^2)-(6x)=o | | (5x-3)(x+1)(x-1)=0 | | 3x-6=5x+60 | | 5y+7=2y+11 | | -13+2x=-52+35x(fraction) | | 10a+b=8a+8b | | 43x+7=16 | | (5x-3)(x+1)(x-1)=(5x+1)(5x-1)x | | 7000=(1+0.0425t) | | 58-2x=8-7x | | 2(y-9)=3Y-8 | | 4(2x-3)-7x+5=11 | | 4x+2x+9+x+4=34 | | (2x+2)(3x^2-x+2)= |